Combination of A Photosystem 1‐Based Photocathode and a Photosystem 2‐Based Photoanode to a Z‐Scheme Mimic for Biophotovoltaic Applications1. Issue 52 (7th November 2013) - Kothe, Tim; Plumeré, Nicolas; Badura, Adrian; Nowaczyk, Marc M.; Guschin, Dmitrii A.; Rögner, Matthias; Schuhmann, Wolfgang
<x xml:space="preserve">Abstract</x> Z‐Scheme on wires: The two photosystems of the natural photosynthetic Z‐scheme have been connected by immobilizing them within redox hydrogels on individual electrodes. Upon irradiation, this biophotovoltaic device produced photocurrents as a closed and autonomous system. The open‐circuit voltage of the cell corresponds to the potential difference between the two redox hydrogels and indicates the coupling of the two charge separation steps.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>